Once I Gazed at You in Wonder : Poems - Levi, Jan Heller (Book collections on Project MUSE., 1999)
A collection of poems by a New York writer. In Sex Is Not Important, she writes: "Have you ever seen / those teenagers clenched / on street corners, / repetitively touching lips? / I think it's because / they have nothing to say."